ASPECT OF JUSTICE ON PROGRESSIVE TARIFF STIPULATION POLICY ON MOTORIZED VEHICLES TAX IN PAPUA PROVINCE - Samosir, Hotlan (Yustisia, 2018)
This study aims to analyze the implementation of progressive tariffs on motorized vehicles in Papua Province based on Regional Legislation Number 4 of 2011 concerning Regional Taxes. The problem studied in this paper is how aspects of democracy and justice are applied in regional legislation in Papua Province. The study was conducted by using a normative juridical research method which is focused on studying the application of norms in positive law. The application of progressive tax on four-wheeled motorized vehicles in Papua Province required review as it contradicted aspects of democracy and justice as mandated by Law Number 28 of 2009 concerning regional taxes and Regional Retributions. The enactment of the law gave a mandate to the region to form and issue a regional legislation as a legal basis for local tax collection. Based on the mandate, Regional Legislation Number 4 of 2011 concerning Regional Taxes in Papua Province was formed. Thus, the application of the regional legislation has not fully appropriate yet due to the factual consideration that the limitation on the number of four-wheeled vehicles in Papua Province is not due as its density is still at the normal level.